Investigation of NV centers in diamond nanocrystallites and nanopillars. Issue 1 (10th September 2012) - Petkov, Emil; Popov, Cyril; Rendler, Torsten; Petkov, Christo; Schnabel, Florian; Fedder, Helmut; Lee, Sang‐Yun; Kulisch, Wilhelm; Reithmaier, Johann Peter; Wrachtrup, Jörg
Abstract Nitrogen‐vacancy (NV) centers were incorporated during hot filament chemical vapor deposition of diamond nanocrystallites and nanocrystalline diamond (NCD) films. From the latter nanopillars with different diameters were prepared applying electron beam lithography and inductively coupled plasma reactive ion etching. The deposition of either single crystallites or closed films was controlled by the nucleation density on the silicon substrates and the process duration. Optical investigations revealed the presence of ensembles of color centers in both nanostructures. An enhancement of the fluorescence emission by an order of magnitude was observed after the structuring of the NCD films.